2022
DOI: 10.1002/zaac.202200044
|View full text |Cite
|
Sign up to set email alerts
|

High pressure torsion, a large‐scale manufacturing tool for high ZT skutterudite thermoelectrics

Abstract: Dedicated to Professor Mercouri Kanatzidis on the occasion of his 65th birthdayFor mass production of thermoelectric generators, a cheap/ sustainable method is required to fabricate leg material with a high figure of merit, ZT. Severe plastic deformation, SPD, increases the defect density, and in parallel decreases the grains to nano-size. SPD via high-pressure torsion, HPT, was used to process hot pressed discs, whereby the Seebeck coefficient remained unchanged and the enhanced electrical resistivity was ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(172 reference statements)
0
3
0
Order By: Relevance
“…Several methods for synthesizing and processing skutterudites have been reported, leading to significant enhancements in their TE performance. , Techniques such as spark plasma sintering or cold sintering process can tailor the skutterudite microstructure and improve ZT . One of the techniques that has yielded significant improvements is high-pressure torsion, HPT, which introduces many grain boundaries as well as dislocations in the structure, enhancing ZT values up to a factor of 2 for some skutterudites . The methodology used in this study can also take into account the influence of grain boundaries on the electronic and thermal transport properties of materials .…”
Section: Resultsmentioning
confidence: 99%
“…Several methods for synthesizing and processing skutterudites have been reported, leading to significant enhancements in their TE performance. , Techniques such as spark plasma sintering or cold sintering process can tailor the skutterudite microstructure and improve ZT . One of the techniques that has yielded significant improvements is high-pressure torsion, HPT, which introduces many grain boundaries as well as dislocations in the structure, enhancing ZT values up to a factor of 2 for some skutterudites . The methodology used in this study can also take into account the influence of grain boundaries on the electronic and thermal transport properties of materials .…”
Section: Resultsmentioning
confidence: 99%
“…High-pressure torsion (HPT) deformation is considered one of the successful approaches to induce high dislocation densities to TE materials, in which high strains are attainable with relatively minimal cracking, as opposed by simple tensile or compression deformation [148][149][150][151][152][153][154][155][156][157][158][159][160][161]. In one of the successful applications of HPT, Rogl et al showed that although the high temperature HPT increased significantly the electrical resistivity of impure DD 0.40-Fe 2.8 Co 1.2 Sb 12 (DD stands for didymium, a binary Nd-4.8 wt% Pr alloy), the enhancement in the Seebeck coefficient (120-210 mV/K @ 800 K) and the drop in the thermal conductivity (35-23 mW/cm•K @ 800 K) led to a zT enhancement from 0.5 of the undeformed sample to 1.38 after deformation [153].…”
Section: Targeting High Zt Through Intentional Plastic Deformationmentioning
confidence: 99%
“…4) The results of recent studies on the applications of HPT for producing advanced materials of different categories were surveyed in a number of publications. They refer to thermoelectric generators, 5) magnetic materials, 6) high entropy alloys, 7) hydrogen storage materials, 8,9) superconducting materials, 10) semiconductors, 11) and hybrid nanocrystalline alloys. 12) Besides, review articles focusing on various aspects of HPT were published.…”
Section: Introductionmentioning
confidence: 99%